If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -9y + 3 = 0 Reorder the terms: 3 + 12x + -9y = 0 Solving 3 + 12x + -9y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + 12x + -3 + -9y = 0 + -3 Reorder the terms: 3 + -3 + 12x + -9y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 12x + -9y = 0 + -3 12x + -9y = 0 + -3 Combine like terms: 0 + -3 = -3 12x + -9y = -3 Add '9y' to each side of the equation. 12x + -9y + 9y = -3 + 9y Combine like terms: -9y + 9y = 0 12x + 0 = -3 + 9y 12x = -3 + 9y Divide each side by '12'. x = -0.25 + 0.75y Simplifying x = -0.25 + 0.75y
| 2x-x^3+5=3 | | 0.3x+0.2(x-7)=8 | | 6x-3=9# | | 2X-6Y=2 | | 9y=x | | 0.5x^4+1=1.25x^3-1 | | 9x+25=4x | | -6x+5=2-3-5x+x | | x^4+x-2=0 | | 4m-5=m-5 | | 7+7x=6x-9 | | 11x+33=5x-129 | | x-(0.03x)=29 | | 6t^2-5t-4=0 | | -14=x+12/-6 | | 3x+8=89-6 | | 2/3w=8 | | 3(x+7)2+17=25 | | 1/2x=3 | | p=25 | | -3/4(12x-8)=-18 | | 20-4x=5x-35 | | a^2+2a+8=0 | | x-6=42 | | 4x+y=-20 | | 2p-1=3y+11 | | 29-H=207 | | 9x-4x+32=6x-21 | | 33=0+3y | | 3y-2y=8x | | y=3/5+9 | | y=2.5x-2 |